Is intra articular injection of triamcinolone acetonide a better option in management for primary osteoarthritis knee than methylprednisolone acetate? - Nath S. H., Syam; Ram, Ganesan G. (International Journal of Research in Orthopaedics, 2019)
Background: Intra articular corticosteroid injections are commonly using in management of osteroarthritis of knee. Most commonly used ones are methylprednisolone acetate (MPA) and triamcinolone acetonide (TA). The aim of our study is to compare the efficacy of these two agents in treating osteoarthritis of knee and find out if any one agent is superior to other if so. Methods: Selected patients with symptomatic OA knee with kellgren-Lawrence grade III were given intra articular steroid injections (40 mg TA or 40 mg MPA) and were reassessed on day 0, 1 month, 3 months and 6 months. VAS and Knee society scores were calculated using questionnaire method and compared the scores. Results: The VAS and KSS was improved significantly on day 0,1 month and 6th month and it was found to be increased at 6th month in both the groups and the values were comparable in both the groups. The effect of both the agents last for 3-6 months and the effects found to be maximum at 1st month and the effects starts to wean off at the end of 6 months in both the groups. Conclusions: Both methylprednisolone acetate (MPA) and triamcinolone acetonide (TA) are equally effective in reducing pain in patients with osteoarthritis of knee and thereby improving their functional ability upto 6 months.